Optimization of the target strategy of perioperative infusion therapy based on monitoring data of central hemodynamics in order to prevent complications - Dmytriiev, Dmytro; Nazarchuk, Oleksandr; Melnychenko, Mykola; Levchenko, Bohdan (Frontiers in Medicine, 2022)
Enhanced Recovery After Surgery (ERAS) protocols are increasingly used in the perioperative period around the world. The concept of goal-directed fluid therapy (GDT) is a key element of the ERAS protocols. Inadequate perioperative infusion therapy can lead to a number of complications, including the development of an infectious process, namely surgical site infections, pneumonia, urinary tract infections. Optimal infusion therapy is difficult to achieve with standard parameters (eg, heart rate, blood pressure, central venous pressure), so there are various methods of monitoring central hemodynamics - from invasive, minimally invasive to non-invasive. The latter are increasingly used in clinical practice. The current evidence base shows that perioperative management, specifcally the use of GDT guided by real-time, continuous hemodynamic monitoring, helps clinicians maintain a patient’s optimal fluid balance. The manuscript presents the analytical data, which describe the benefits and basic principles of perioperative targeted infusion therapy based on central hemodynamic parameters to reduce the risk of complications.